Characteristics of Policy Networks in Two Finnish EU Funded Projects - Vahvelainen, Heli (My University, 2002)
European Union Structural Funds and Regional Policies implementation have been oriented to involve the sub-national level of government to plan, act and co-ordinate EU activities more than before. At the same time relations between the regional authorities and project leaders are seldom studied. Thus, the aim of this thesis is to understand better the nature of EU funded projects. This aim is approached by studying relations between the regional authorities, project leaders and participants in the projects through policy networks. Specified research questions focused the target: What type and dimensions of policy networks, and elements of network evolution can be perceived in the selected Finnish EU funded projects? How does the characteristic features defining the type and the content of policy network dimensions appear in the two selected cases? Can a model for network evolution and its stages be applied to and distinguished in the two selected cases? How does partnership appear in the selected cases? Characteristics are studied by using a multiple case study method with impacts from qualitative network analyses. The material for the theoretical part is a result of examining academic literature whereas data for case analyses is collected through interviews and phone interviews from actors participating in the selected projects. In addition documents such as Steering Committee minutes and annual reports are used. The main concepts are ‘policy network’ and ‘partnership’. They are chosen because they reveal network discussion evolving in society and affecting eventually every administrative relation. Thus selected projects are scrutinised by distinguishing their elements and characteristics in order to allocate them to correspond a certain type or dimension of policy network. The types of policy networks in this study are policy communities, issue-, producer-, professional-, and intergovernmental networks. Dimensions used are the type of actors, integration, resources and power. Network evolution was estimated by distinguishing different stages from the projects. The idea of partnership was emphasised by discovering relations to which long-term, complementary and goal oriented targets in co-operation are prominent. Main findings show that intermediary structures of policy networks are dominating. In the first case of joint purchasing in agriculture, the project was considered closer to policy community whereas the recycling of furniture project had more elements characteristics for issue network. The type of actors depends on the substance of the project. In the case related to agriculture the position of rural interests was strong whereas recycling of furniture project included a high variety of different interests. Integration seems to increase between the actors during the project. In addition integration may be concentrated on core participants. Actors deliver and change resources, which are often complementary. Further, evolutionary cycle could be applied to the projects and with it progressing projects could be explained. The long common history of actors promotes to continue partnering after the project. Establishing a new project takes longer from the actors that are new to each other. The conditions for successful partnership are that actors have long-term orientation for co-operation, they are not competitors even though it is not the absolute truth and they have complementary resources to change.
Keywords: policy network; partnership; European Union Structural Funds; regions; projects; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|